The Effects of Tunneling Incentive, Bonus Mechanism, and Firm Size on Transfer Pricing - Rochmah, Annisa; Kesumo Wardhani, Nurhastuty (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This research is conducted to examine how tunneling incentive, bonus mechanism, and firm size influence transfer pricing among banking companies listed on the Indonesia Stock Exchange (IDX) throughout 2022–2024. The study employs a purposive sampling technique, selecting data from annual reports of banks that meet predetermined criteria, yielding a total of 102 firm-year observations. The analysis utilizes panel data regression to test the hypotheses. Findings reveal that both tunneling incentive and bonus mechanism positively affect transfer pricing, indicating that the personal motives of majority shareholders and performance-based managerial rewards may stimulate transfer pricing behavior. Conversely, firm size shows a negative relationship with transfer pricing, suggesting that larger institutions tend to limit such activities due to greater oversight from regulators. The outcomes of this research offer meaningful implications for policymakers, investors, and corporate leaders in comprehending the determinants of transfer pricing practices within the banking industry.